Circuit reliability estimation based on an iterative PTM model with hybrid coding. (June 2016) - Xiao, Jie; Lee, William; Jiang, Jianhui; Yang, Xuhua
Abstract: Using the probabilistic transfer matrix model as the major technology, this paper firstly separated the presentation and quantification of signal relations, and blocked the concurrent signals in fan-out by hybrid coding; secondly a method to construct the output reliability matrixes and output probability distributions of basic circuit components was proposed based on a virtual method; and then a method to achieve the reliability iterative propagation between the pre-stage and post-stage circuit was designed using a weak equivalence principle. The theoretical analysis and experiment results show that the proposed method can be applied to the reliability evaluation for several-abstract-level circuits that have high calculation precision and linear complexity in time and space. Highlights: A fast and highly accurate evaluation method for circuit reliability was proposed based on probabilistic transfer matrix model with hybrid coding. An iterative strategy for reliability propagation was proposed based on a virtual method and a weak equivalence principle. The method can be applied to the reliability evaluation for several-abstract-level circuits.